“Into Memory It Is Engraved – In Memory It Is Treasured – From Memory It Fades”. On the Perception of Memory in Conversations With Witnesses of History on the Example of the Archives of the Warsaw Rising Museum - Przyklenk, Joanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
The aim of this article is to discuss the ways in which memory is perceived in genologically homogeneous texts. The subject of the research is the word pamięć (ang. “memory”) recalled by a witness of history or by a person interviewing him/her. The texts constituting the Oral History Archive of the Warsaw Rising Museum were the source of the analyses. The linguistic view of the phenomenon of memory made use of such concepts as the linguistic image of the world, the assumption of the genological and discursive specificity of each text, and collective memory. It was established that the use of the word memory by both the questioners and the narrators indicates its receptacle character, i.e. seeing memory as a place where elements of the past are stored, with the image of memory in the narrators’ account being dynamised. The second of the meanings is also actualised in the statements of the narrators, capturing memory as a specific capacity of the human mind, which the veterans subject to metareflection, assessing it as good, weak or incomplete. They recognise its malleable and changeable character. Witnesses also use the word memory in a third meaning, i.e. to recall the memory of past persons or events in order to honour them.